The effectiveness of kindness training on academic resilience and interpersonal forgiveness of Female Students of the Third Grade of the High School - Faramarz Sabeghi (مطالعات روانشناسی تربیتی)
The Porpouse of this study was to investigate the effectiveness of kindness training on academic resilience and interpersonal forgiveness. An experimental design was employed with pretest, posttest and control group. The population of this study included all female students of the third grade of high school in Zahedan city in the academic year 2022-2023. The sample consisted of 30 students which were randomly selected in two groups of 15 experimental and control. The data collection instrument was questionnaires on academic resilience and interpersonal forgiveness that all participants completed as the pre-test. Then, the kindness training was conducted in the experimental group for eight sessions. Finally, the same questionnaire was completed by both experimental and control groups. Then, the data was analyzed using covariance analysis. The findings indicated kindness training can affect academic resilience and interpersonal forgiveness. The findings indicated kindness training can affect academic resilience and interpersonal forgiveness. The findings indicated kindness training can affect academic resilience and interpersonal forgiveness.. According to the results of this research, it is suggested to develop a program of teaching kindness in schools in order to increase resilience and interpersonal forgiveness of students.